Hubungan Pengetahuan dan Sikap Remaja Putri terhadap Kepatuhan Mengonsumsi Tablet Fe - Layuk, Nurrahma; Deivita, Yan; Siregar, Asni Annisa; Saraha, Rosida Hi; Putri, Anira Sukma Sukardi (JIDAN Jurnal Ilmiah Bidan, 2025)
Background: Anemia is a condition when the concentration of red blood cells is below normal. Adolescent girls are susceptible to anemia due to inadequate nutritional intake, as well as physiological factors such as menstruation which causes adolescent girls to lose about 1.3 mg of blood per day, the possibility of pregnancy and abortion. Objective: The purpose of this study was to determine the relationship between knowledge and attitudes of adolescent girls regarding compliance with Fe tablet consumption. Methods: The research method used a descriptive analytical design with a cross-sectional approach. The population in this study were all adolescent girls at SMA IT and the research sample was 30 adolescent girls based on a very small population, so the sample of 30 became large or more than 75% of the population. Result: The results showed that 12 respondents (40%) had a good level of knowledge, 10 respondents (33.3%) with a sufficient level of knowledge and 8 respondents (26.7%) with a low level of knowledge. The proportion of adolescents who were obedient in consuming Fe tablets was more dominant in the good knowledge group (40%), while in the low knowledge group it was only 13%. Chi-Square test analysis using SPSS version 27 with a result of P <0.05 showed a relationship between knowledge and attitudes of adolescent girls in compliance with consuming Fe tablets. The results of the Odds Ratio (OR) analysis were 10.286, indicating that the chance of compliance in consuming Fe tablets was 10 times higher compared to respondents who commented negatively. Conclusion: The conclusion of the study showed that the level of knowledge and attitude of adolescent girls was significantly related to compliance in consuming Fe tablets. Further research is suggested to explore forms of educational interventions such as using educational video media to improve knowledge and attitudes in consuming Fe tablets.